A method for reliability detection of automated guided vehicle based on timed automata. Issue 1 (1st January 2021) - Deng, Xuefeng; Zhou, Bingqian; Sun, Xinyi; Yang, Hua; Chen, Lingyu
Abstract : To ensure the normal operation of the automated guided vehicle, the system must pass the reliability test in the process of design and manufacturing. Unreliable events are small probability events, which is not easy to be detected by using experimental methods. Besides, a lot of testing work is needed. In this paper, a time automata based reliability detection method of automated guided vehicle is proposed and the model of the vehicle is built in the design stage.The counting function related to reliability calculation is introduced to record the occurrence number of reliability-related events. The timed automata is used to qualitatively test the design model of the automated guided vehicle. After the model is proved to be correct, the timed automata model of the automated guided vehicle is automatically iterated by using the simulation function of the model detection tool. The simulation data can be used to quantitatively test the reliability of the design model of the automated guided vehicle. The simulation results show that the proposed method can calculate the reliability of the automated guided vehicle for the design stage. The reliability is evaluated quantitatively to provide reliability guarantee for engineering design.